Simultaneous Quantification of 25-Hydroxyvitamin D3 and 24,25-Dihydroxyvitamin D3 in Rats Shows Strong Correlations between Serum and Brain Tissue Levels - Ying Xue; Xin He; Huan-De Li; Yang Deng; Miao Yan; Hua-Lin Cai; Mi-Mi Tang; Rui-Li Dang; Pei Jiang (International Journal of Endocrinology)
While vitamin D3 is recognized as a neuroactive steroid affecting both brain development and function, efficient analytical method in determining vitamin D3 metabolites in the brain tissue is still lacking, and the relationship of vitamin D3 status between serum and brain remains elusive. Therefore, we developed a novel analysis method by using high performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) to simultaneously quantify the concentrations of 25-hydroxyvitamin D3 (25(OH)D3) and 24,25-dihydroxyvitamin D3 (24,25(OH)2D3) in the serum and brain of rats fed with different dose of vitamin D3. We further investigated whether variations of serum vitamin D3 metabolites could affect vitamin D3 metabolite levels in the brain. Serum and brain tissue were analyzed by HPLC-MS/MS with electrospray ionization following derivatization with 4-phenyl-1,2,4-triazoline-3,5-dione (PTAD). The method is highly sensitive, specific, and accurate to quantify 25(OH)D3 and 24,25(OH)2D3 in animal brain tissue. Vitamin D3 metabolites in brain tissue were significantly lower in rats fed with a vitamin D deficiency diet than in rats fed with high vitamin D3 diet. There was also a strong correlation of vitamin D3 metabolites in serum and brain. These results indicate that vitamin D3 status in serum affects bioavailability of vitamin D3 metabolites in the brain.